The role of conciliation in settling administrative disputes (A comparative study) (Journal of Misan Researches, 2020)
The idea of ​​the research stems from the necessity of accompanying the Iraqi legislator to the comparative procedural legislations that have been used as administrative means as a means of resolving administrative disputes, due to its speed in resolving disputes, and because it leads to an improvement in the relationship between management and citizens, and saves on public expenditures, and reconciliation is distinguished from procedural concepts Others in resolving disputes (abandonment, assignment, and arbitration), because it is a contractual behavior that ends or avoids a dispute by mutual concessions. In order to detail this topic, its treatment came in two topics through which we can shed light on the issue of conciliation in administrative disputes. The first topic will be devoted to studying the concept of conciliation in administrative disputes. The legal justification for conciliation, and its justifications. As for the second topic, it was devoted to discuss the legal framework for conciliation in administrative disputes, and we will divide it into two requirements. In the first demand, we will address the legal basis for conciliation in comparative and Iraqi legislation, and in the second demand we review the reconciliation procedures and the effects of .